URBAN RESILIENCE: A SYSTEMATIC REVIEW OF THE INTERPLAY BETWEEN POVERTY, GOVERNANCE, AND SUSTAINABILITY - Durba Dutta (International Journal For Research In Educational Studies, 2023)
This systematic review evaluates the literature on urban poverty, good governance, and sustainable development from 2010 to 2024. Understanding the interplay between governance and sustainability is crucial for addressing urban poverty. The review examines various systematic and analytical methods and analyses key factors affecting urban sustainability, including social inclusion, governance, and technology. Findings reveal that sustainability initiatives often neglect social inclusion, underscoring the need to integrate vulnerable groups. The review addresses governance trade-offs, the effectiveness of smart governance, and the role of Urban Sustainability Indicators (USIs) in achieving Sustainable Development Goals (SDGs). It also discusses the environmental impacts of economic development in urban areas and the ongoing challenges of urban poverty. Special attention is given to North America, Nigeria, and Indonesia, highlighting that despite regional differences, urban poverty remains a concern across these diverse areas. Good governance is crucial for alleviating urban poverty and advancing sustainable development by fostering inclusive policies, efficient management, and community involvement. Effective governance ensures that public institutions are accountable and responsive to citizen needs. Sustainable urban development involves balancing economic, social, and environmental dimensions to create liveable cities that meet present and future needs. This includes strategies such as affordable housing, clean energy, waste management, and green spaces. Proper urban planning can lead to job creation, better education, and improved quality of life, while poor planning can result in slums, inequality, and deprivation. Innovations like AI offer potential solutions for addressing urban poverty through enhanced governance, but a collective and evidence-based approach is essential. The review highlights the need for strategic planning and interdisciplinary integration to tackle urban development challenges effectively, emphasizing the importance of data-driven and inclusive policies.